Stereodivergent synthesis of vicinal quaternary-quaternary stereocenters and bioactive hyperolactones - Haifeng Zheng (Nature Portfolio, 2018)
Stereodivergent construction of adjacent quaternary-quaternary stereocenters remains a formidable synthetic challenge. Here, the authors report a nickel-catalyzed enantioselective dearomatization Claisen rearrangement leading to vicinal all-carbon stereocentres and apply it to the stereodivergent synthesis of bioactive hyperolactones.